Pricing of orphan drugs in oncology and rare diseases. Issue 1 (1st January 2020) - Nuijten, Mark; Capri, Stefano
ABSTRACT: Objective: The objective of this paper is to determine an upper price limit for an orphan drug by taken a broader perspective and, including also other monetary and non-monetary values for the society. Methods: This model is based on the expected free cash flows and the required minimum rate of return for the investor. In addition we calculated an innovation premium resulting from cost savings due to the substitution effect and the monetary gain in QALYs of a new medicine. We selected Spinraza®, a first in class drug with only best supportive care as comparator, and Perjeta®, a first in class drug with already an actual treatment as comparator. Results : The results show that Spinraza® leads to an innovation premium of € 78, 966 and Perjeta® shows an innovation premium of € 4, 388, because there were no cost savings. The analyses show the outcomes are sensitive to discount rate for QALYs. Conclusion: The break-even price from only an investor perspective may not reflect the value of drug from a broader perspective. This study shows drug prices based on an innovation premium may be more representative of the actual value of innovation for the society.